Narrative Analysis of Female Leadership in Novel Asiyah The Rose of Pharaoh Desert By Sibel Eraslan - Wimeta Islam Sabila; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe how the depiction of female leadership, namely Queen Aisyah in the era of the Egyptian kingdom in the novel with the same title by Sibel Eraslan. This research uses analisis narrative theory by Algirdas Greimas, three structural that focuse on relations theories, and gender theory by Backman and D’Amico. Data collection was used by reading every page of text in Asiyah's novels completely, and assisted by literature from book sources, previous research, scientific journals, and several articles from the internet. The method used is qualitative with a descriptive approach. The results showed that Asiyah, who is the main character in the novel, is not always in the subject position. Queen Asiyah's character, character, attitude, and reaction to something that is seen directly are more dynamic in nature. Based on the stereotypes of Gender Beckman and D'Amico, Asiyah’s leadership during her time as queen of the Egyptian empire showed traits and behaviors that were more towards a feminine who was gentle, wise and more oriented to build very noble relationships. The research explanation that shows the good and noble portrayal of Ratu Aisyah's leadership is also supported by the narrative and dialogue between Asiyah and several characters in the novel's story.